Breast Cancer Assistance Journey from the perspective of the Public Healthcare Service of Rio Grande do Sul - Anschau, Fernando; Bedin, Sabrina; Kopittke, Luciane; de Camargo Martins, Tamie; Grigolon, Ruth; Monteiro, Isabel; da Cunha Varolli, Giovanna; Luz, Rodrigo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2024)
Objective: This study aims to characterize the breast cancer (BC) patient journey in Rio Grande do Sul (RS), Brazil, through the perspectives of the High Complexity Oncology Assistance Centers (CACONs) and High Complexity Oncology Assistance Units (UNACONs). Methods: Conducted between March and May 2023 across 17 RS Oncology public healthcare services, the cross-sectional study utilized a 54-question questionnaire administered to healthcare professionals. The survey covered various aspects, including diagnosis, treatment, funding, and multidisciplinary teamwork. We put special emphasis on the time of diagnosis and treatment, as Law No. 12,732/12 mandates that the first oncological treatment must begin within 60 days. Results: Descriptive analysis revealed that BC patients undergo screening tests upon treatment entry (88.2%), with immunohistochemistry commonly performed externally (64.7%) and PCR often requested (82.4%) for adjuvant therapy initiation, taking an average of 90 to 250 days for all procedures. Patients encounter challenges such as lengthy hospital stays, extensive travel to treatment centers, treatment side effects, and high transportation expenses, often leading to treatment discontinuation. The most time-consuming stage is treatment, with subcutaneous infusion proving more time-efficient than intravenous administration. Physical limitations, mobility issues, late diagnosis (90-day average), and limited access to care significantly impact patients’ quality of life. Healthcare teams face difficulties with outdated guidelines, lack of intravenous treatment facilities, and extended administration durations. Institutions confront barriers like drug shortages, guideline disparities, and logistical challenges. Conclusion: The study concludes by emphasizing the identified hurdles in BC patients’ public healthcare journey, underscoring the need to address delays in screening, resource constraints, and disparities in access to care based on geographical, socioeconomic, and racial/ethnic factors to enhance overall quality of care and equity within the system.